Differential effects of macro and micro country images by product category and by country among Saudi consumers. Issue 8 (13th August 2018) - Jin, Byoungho; Almousa, Moudi O.; Yang, Heesoon; Kim, Naeun
Abstract : Purpose: While country image consists of two hierarchical images – macro country image at the country level and micro country image at the specific product level – previous studies have largely failed to detail its varying effects by product category and by the level of a country's economic development. The purpose of this paper is to examine the impact of the macro and micro country images of four countries (USA, Italy, Korea, and Malaysia) on Saudi consumers' purchase intentions in two product categories (symbolic and functional product). Design/methodology/approach: Data were collected from shoppers older than 20 years of age at several shopping malls in Riyadh, Saudi Arabia via mall intercept method. Findings: Analyses of 496 data revealed that the effects of macro and micro country images differ by product category. In particular, both macro and micro country images were equally relevant to the purchase intention of symbolic goods (i.e. handbags), while micro country image played a greater role in the purchase intention of functional goods (i.e. cell phones). A partial country moderating effect was found. The effects of micro country image on the purchase intention of handbags were valid only in Italy, where product-country match is high. Originality/value: This study advances country image research by highlighting how the effects of macro and micro country images on purchase intention differ by product category and by country. The findings suggest which aspect of country image (i.e. macro vs micro) should be actively communicated in the marketing of symbolic and functional goods.